Borane promoted aryl transfer reaction for the synthesis of α-aryl functionalised β-hydroxy and β-keto esters. Issue 21 (16th May 2022) - Kaehler, Tanja; Lorenz, Jonas; Ould, Darren M. C.; Engl, Dorothea; Santi, Micol; Gierlichs, Lukas; Wirth, Thomas; Melen, Rebecca L.
Abstract : The synthesis of a series of α-aryl or α-alkyl functionalised β-hydroxy and β-keto esters has been achieved by reacting α-diazoesters with boranes, and aldehydes, ketones, anhydrides, nitriles, esters or isocyanates. Abstract : The synthesis of a series of α-aryl or α-alkyl functionalised β-hydroxy and β-keto esters has been achieved by reacting α-diazoesters with boranes, and aldehydes, ketones, anhydrides, nitriles, esters or isocyanates. In a mild reaction protocol, 26 examples are presented in yields up to 73%.